2020
DOI: 10.3390/su12156128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evacuation Strategies According to the Travel Demand: The Case of Nuclear Research Reactor HANARO’s EPZ

Abstract: In the event of a nuclear accident, evacuation is the most effective protective action for the public. During the evacuation, total travel time is a key measure to protect the public because it is directly related to the public’s radiation exposure. Thus, strategies that reduce the total travel time are needed for a safer nuclear emergency plan. Many studies on evacuation strategies so far have suggested the methodology of effective routing decisions or delay management. Despite the application of those strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[1] In the aftermath of such incidents, substantial focus has been placed on evacuation strategies, with numerous studies aiming to optimize evacuation processes and accurately predict evacuation times. [2][3][4] However, while the evacuation of general public is crucial, equally important is the rapid assembly of emergency staff required to stabilize the affected nuclear power plant. Recognized within South Korea's Accident Management Program [5], the guidelines specify that emergency staff assembly must be completed swiftly to ensure effective incident management.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In the aftermath of such incidents, substantial focus has been placed on evacuation strategies, with numerous studies aiming to optimize evacuation processes and accurately predict evacuation times. [2][3][4] However, while the evacuation of general public is crucial, equally important is the rapid assembly of emergency staff required to stabilize the affected nuclear power plant. Recognized within South Korea's Accident Management Program [5], the guidelines specify that emergency staff assembly must be completed swiftly to ensure effective incident management.…”
Section: Introductionmentioning
confidence: 99%
“…Vegsoova et al found that smaller emergency groups resulted in longer evacuation times [3]. Kim et al demonstrated that travel demand levels affect the effectiveness of evacuation strategies [4].…”
Section: Introductionmentioning
confidence: 99%